THE RELATIONSHIP BETWEEN PERSONAL HYGIENE PATTERNS AND DERMATITIS INCIDENTS AMONG HORTICULTURAL FARMERS IN SENDANGAGUNG - Theresia Avila Evi Kustanti; Karunia Estri, Arimbi; Ratnawati, Emmelia (Rifapublisher.id, 2024)
Background: Contact dermatitis is an inflammation of the skin caused by pesticides and chemical fertilizers that adhere to the skin. Personal hygiene is one of the indirect causes of contact dermatitis. Based on epidemiological data in Indonesia in 2017, 97% of 389 cases of skin diseases were contact dermatitis. Of these, 66.3% were irritant contact dermatitis and 33.7% were allergic contact dermatitis. In 2018, the national prevalence of dermatitis in Indonesia was 6.8%. Dermatitis ranked 17th at the Minggir Community Health Center for outpatient patients from January to February 2023. This research was conducted from June 25 to June 19, 2023. Objective: The purpose of this study was to determine the relationship between personal hygiene patterns and dermatitis among horticultural farmers in Sendangagung Village, Minggir Sub-district. Method: This quantitative research used an analytical observational study with a Cross-Sectional Study approach and employed Total Sampling with 61 samples. Instruments used included a questionnaire on personal hygiene patterns, a questionnaire on contact dermatitis, and observation of contact dermatitis. Results: Most respondents did not use personal protective equipment (PPE), amounting to 13 individuals (21.3%), and all horticultural farmers who used PPE did not use it properly, totaling 48 individuals (78.7%). Respondents with poor personal hygiene patterns were very few, totaling 8 individuals (13.1%). A small number of respondents experienced contact dermatitis, totaling 19 individuals (31.1%). Bivariate analysis using Fisher's exact test yielded a p-value of 0.001 (p-value < 0.05), indicating a significant relationship between personal hygiene patterns and the occurrence of dermatitis among horticultural farmers. Conclusions: There is a significant relationship between personal hygiene patterns and the occurrence of dermatitis among horticultural farmers in Sendangagung Village, Minggir Sub-district.